Excited-state quantum phase transitions in finite many-body systems. (29th October 2015) - Cejnar, Pavel; Stránský, Pavel; Kloc, Michal
Abstract: Quantum spectra of excited states of numerous collective many-body models show singularities related to stable and unstable stationary points of the corresponding classical dynamics. We show several examples of these singularities and discuss some of their consequences.